2008
DOI: 10.2169/internalmedicine.47.0656
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Summer-type Hypersensitivity Pneumonitis Initially Misdiagnosed as Idiopathic Interstitial Pneumonia

Abstract: The clinical features of chronic hypersensitivity pneumonitis (HP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A number of species colonise the skin, gastrointestinal, respiratory and urinary tracts of humans [2], [3], and superficial Trichosporon infections of immunocompetent individuals such as white piedra infections of the hair shaft are well documented [2], [3]. As well as superficial infections, repeated inhalation of Trichosporon arthroconidia can cause summer-type hypersensitivity pneumonitis (SHP) [4], [5], an immunologically induced lung disease. It is the most common form of hypersensitivity pneumonitis (HP) in Japan [4] and T. asahii is the most frequent cause of the disease [1], [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of species colonise the skin, gastrointestinal, respiratory and urinary tracts of humans [2], [3], and superficial Trichosporon infections of immunocompetent individuals such as white piedra infections of the hair shaft are well documented [2], [3]. As well as superficial infections, repeated inhalation of Trichosporon arthroconidia can cause summer-type hypersensitivity pneumonitis (SHP) [4], [5], an immunologically induced lung disease. It is the most common form of hypersensitivity pneumonitis (HP) in Japan [4] and T. asahii is the most frequent cause of the disease [1], [3].…”
Section: Introductionmentioning
confidence: 99%
“…As well as superficial infections, repeated inhalation of Trichosporon arthroconidia can cause summer-type hypersensitivity pneumonitis (SHP) [4], [5], an immunologically induced lung disease. It is the most common form of hypersensitivity pneumonitis (HP) in Japan [4] and T. asahii is the most frequent cause of the disease [1], [3]. However, other fungi such as the basidiomycete yeast Cryptococcus may be responsible for SHP [6] and accurate identification of the causative species is necessary for appropriate treatment, which is challenging due to the number of different techniques required [7][10].…”
Section: Introductionmentioning
confidence: 99%
“…The histopathological findings in chronic HP have been described recently, 4–7 but histological features overlap with other idiopathic interstitial pneumonias, especially idiopathic pulmonary fibrosis (IPF) 8,9 . Indeed, some cases diagnosed initially as IPF have been confirmed later to be chronic summer‐type HP 10,11 . Furthermore, the causative antigen can be difficult to determine 12 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Indeed, some cases diagnosed initially as IPF have been confirmed later to be chronic summer-type HP. 10,11 Furthermore, the causative antigen can be difficult to determine. 12 Several studies have demonstrated good prognosis in patients with chronic HP showing patterns of non-specific interstitial pneumonia (NSIP) and organizing pneumonia (OP), but worse prognosis in those with the usual interstitial pneumonia (UIP) pattern.…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiologic survey for determining chronic HP cases among 36 Japanese cases [9] revealed that the proportion of patients with S-HP who developed chronic HP was smaller than that of the pa- [22] reported problems in the diagnoses of patients with chronic S-HP. They further cautioned that some cases with bird fancier's lung were misdiagnosed as idiopathic interstitial pneumonia (IIP) or chronic and insidious HP before referral to their institution [19][20][21][22]. The data shown in Figure 1 indicates that the patient group comprised 3 subgroups categorized in terms of the time elapsed from the onset of initial symptoms to the time of referral to our hospital.…”
Section: Discussionmentioning
confidence: 99%